New paradigms for BRCA1/BRCA2 testing in women with ovarian cancer: results of the Genetic Testing in Epithelial Ovarian Cancer (GTEOC) study. Issue 10 (12th May 2016) - Plaskocinska, Inga; Shipman, Hannah; Drummond, James; Thompson, Edward; Buchanan, Vanessa; Newcombe, Barbara; Hodgkin, Charlotte; Barter, Elisa; Ridley, Paul; Ng, Rita; Miller, Suzanne; Dann, Adela; et al.
Abstract : Background: Over recent years genetic testing for germline mutations in BRCA1/BRCA2 has become more readily available because of technological advances and reducing costs. Objective: To explore the feasibility and acceptability of offering genetic testing to all women recently diagnosed with epithelial ovarian cancer (EOC). Methods: Between 1 July 2013 and 30 June 2015 women newly diagnosed with EOC were recruited through six sites in East Anglia, UK into the Genetic Testing in Epithelial Ovarian Cancer (GTEOC) study. Eligibility was irrespective of patient age and family history of cancer. The psychosocial arm of the study used self-report, psychometrically validated questionnaires (Depression Anxiety and Stress Scale (DASS-21); Impact of Event Scale (IES)) and cost analysis was performed. Results: 232 women were recruited and 18 mutations were detected (12 in BRCA1, 6 in BRCA2 ), giving a mutation yield of 8%, which increased to 12% in unselected women aged <70 years (17/146) but was only 1% in unselected women aged ≥70 years (1/86). IES and DASS-21 scores in response to genetic testing were significantly lower than equivalent scores in response to cancer diagnosis (p<0.001). Correlation tests indicated that although older age is a protective factor against any traumatic impacts of genetic testing, no significant correlation exists between age and distress outcomes. Conclusions: The mutation yield in unselected women diagnosed with EOC from a heterogeneous population with no founder mutations was 8% in all ages and 12% in women under 70. Unselected genetic testing in women with EOC was acceptable to patients and is potentially less resource-intensive than current standard practice.